Transmission line with vaporous and gaseous cavitation - Chia, Yi Ting (2014)
This study presents a complete research on the transmission line with vaporous and gaseous cavitation. The aim of the project is to improve the performance and reliability of systems and thus able to predict the onset and degree of cavitation taking place.